Representation and Reception of the Image of the Zulu. From Travel Accounts to the Public Sphere in Mid-Victorian and Edwardian Great Britain (1850–1914) - Patricia Crouan-Véron (Cahiers Victoriens et Edouardiens)
As opposed to the accounts of the first European travellers (the Boers) who landed in Southern Africa in 1652, most travel writings of the second part of the nineteenth century and the beginning of the twentieth century were aimed at a wide audience as large extracts from their diaries and travel accounts were published in the press. These written descriptions have become precious sources for the contemporary readers and scholars as they produce knowledge on local ethnic groups living in distant places at that period and they also inform on the people who met them for the first time. Should we consider these representations (most of them were accompanied by sketches and pictures) as truthful and reliable? We will analyse them focusing on the representation of Zulu people. We will try to determine if the representations took different forms whether they were produced by missionaries, traveller-artists or scientists. To what extent does the individual experience become a collective experience? What was the impact of these representations on the Victorian and Edwardian people?